Evaluation of Rumensin® in late season, salt-limited, protein supplements fed to grazing steers and heifers - Corah, L.R.; Brazle, F.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Even though an average daily Rumensin® consumption of over 100 mg per was achieved in all three trials, it did not significantly improve daily gains of steers or heifers grazing late-season native range. Late-season protein supplementation improved average daily gain by over .2 lb per head.
Keywords: Beef; Rumensin®; Protein; Salt